An omnipresent diversity and variability in the chemical composition of atmospheric functionalized organic aerosol. Issue 1 (December 2018) - Ditto, Jenna; Barnes, Emily; Khare, Peeyush; Takeuchi, Masayuki; Joo, Taekyu; Bui, Alexander; Lee-Taylor, Julia; Eris, Gamze; Chen, Yunle; Aumont, Bernard; Jimenez, Jose; Ng, Nga; et al.
Abstract The atmospheric evolution of organic compounds encompasses many thousands of compounds with varying volatility, polarity, and water solubility. The molecular-level chemical composition of this mixture plays a major, yet uncertain, role in its transformations and impacts. Here we perform a non-targeted molecular-level intercomparison of functionalized organic aerosol from three diverse field sites and a chamber. Despite similar bulk composition, we report large molecular-level variability between multi-hour organic aerosol samples at each site, with 66 ± 13% of functionalized compounds differing between consecutive samples. Single precursor environmental laboratory chamber experiments and fully chemically-explicit modeling confirm this variability is due to changes in emitted precursors, chemical age, and/or oxidation conditions. These molecular-level results demonstrate greater compositional variability than is typically observed in less-speciated measurements, such as bulk elemental composition, which tend to show less daily variability. These observations should inform future field and laboratory studies, including assessments of the effects of variability on aerosol properties and ultimately the development of strategic organic aerosol parameterizations for air quality and climate models. The detailed molecular-level speciation of organic aerosol is a highly challenging task. Here, the authors show an extensive molecular-level intercomparison of functionalized organic aerosol from three diverse field sites revealing large compositional variability between samples at each field site.